Polyphenol Content and Antioxidant Activity of an Endemic Plant of Algerian Sahara: Anvillea radiata - Belakredar, Amal; Hachem, Kadda; Boudou, Farouk; Benabdesslem, Yasmina (Polish Journal of Natural Sciences, 2023)
This study was carried out to assess the main secondary metabolites contents of Anvillea radiata plant using four solvents of increasing polarities (hexane, dichloromethane, methanol, and water), and three complementary antioxidant tests: total antioxidant capacity assay, DPPH free radical-scavenging ability, and ferric reducing antioxidant power (FRAP) assay. Methanol and Aqueous extracts recorded the highest extract yields (20.49±0.26 % and 11.58±0.23% respectively). Dichloromethane extract showed the highest rate of total phenols, flavonoids, and tannin contents (114.45±0.02 mg GAE/g d.w., 245.21±0.07 mg CE/g d.w., and 101.765±0.014 mg CE/g d.w respectively). Dichloromethane and Methanol extracts recorded a significantly high rate in total antioxidant activity (14.41±0.009 and 9.55±0.0023 mg GAE/g d.w. respectively) and exhibited a significant ability to scavenge DPPH radical (IC50 values = 0.9±0.026 and 1.75±0.051 mg/mL respectively) and a significant iron reducing power (EC50 = 0.98±0.034 and 1.31±0.043 mg/ml respectively). These results prove that A. radiata could indeed be a potential source of natural antioxidant and could be of considerable interest for the development of new medicines based on local plants to enhance the natural resources of the national heritage.